Article RETRACTED due to manipulation by the authors The influence of performance in training on self-confidence of wheelchair athletes with coach-athlete intimacy as a moderating variable - Hamzah Latief; Wawan Sundawan Suherman; Cerika Rismayanthi; Abdul Alim; Wedi S; Muchamad Samsu Huda; Wahyu Dwi Yulianto; Trisnar Adi Prabowo (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study aims to analyse the self-confidence of wheelchair basketball, tennis, badminton, and archery athletes. This study uses a moderated regression analysis (MRA) approach, namely performance in training as independent variable, self-confidence as a dependent variable, and coach-athlete intimacy as a moderator. Sampling was done using total sampling at the open tournament championship. The wheelchair athletes involved were 20 basketball athletes, 15 tennis athletes, 15 badminton athletes, and 15 archery athletes age 29.98±2.4 with 11.37±1.2 years of training. The highest experience of the competition is that 37 athletes have participated at the national and international level. This study was conducted for six months from early June to November 2023. The data were collected using questionnaires that were confirmed and given before the match and semi-structured interviews to strengthen the discussion. The instrument consists of 57 items, and an Aiken V validity value of 0.863 and Cronbach’s Alpha value of 0.708 were obtained. The results showed that performance in training influenced self-confidence (sig. 0.003 or p<0.05) and (R2 = 12.8%). Meanwhile, the coach-athlete intimacy can positively moderate the performance of the coach-athlete with self-confidence (sig. 0.000 or p<0.05) and (R2 = 47.2%). The results of this study suggest the involvement of government agencies to foster, develop, and facilitate all individuals with special needs. In addition, it is necessary to increase the competence of coaches through special training or by opening a coach study program for coaching people with disability at the university. Further research should consider the number of samples involved and how to collect data with a research design adapted to the circumstances but can produce accurate data.